Risk of uveitis and inflammatory bowel disease in people with psoriatic arthritis: a population-based cohort study. Issue 2 (1st November 2017) - Charlton, Rachel; Green, Amelia; Shaddick, Gavin; Snowball, Julia; Nightingale, Alison; Tillett, William; Smith, Catherine H; McHugh, Neil
Abstract : Objectives: To determine the risk of uveitis and inflammatory bowel disease (IBD) in patients with psoriatic arthritis (PsA) compared with the general population and patients with psoriasis. Methods: A cohort study using data from the UK Clinical Practice Research Datalink between 1998 and 2014. Patients with incident PsA aged 18–89 years were identified and matched to a cohort of patients with psoriasis and a general population cohort. The incidence of uveitis, all IBD, Crohn's disease and ulcerative colitis was calculated for each study cohort and adjusted relative risks (RRadj ) were calculated using conditional Poisson regression. Results: 6783 incident cases of PsA were identified with a median age of 49 years. The risk of uveitis was significantly higher in the PsA cohort than in the general population and psoriasis cohorts (RRadj 3.55, 95% CI 2.21 to 5.70 and RRadj 2.13, 95% CI 1.40 to 3.24, respectively). A significant increase was observed for Crohn's disease (RRadj 2.96,  95% CI 1.46 to 6.00 and RRadj 3.60,  95% CI 1.83 to 7.10) but not for ulcerative colitis (RRadj 1.30,  95% CI 0.66 to 2.56 and RRadj 0.98,  95% CI 0.50 to 1.92). Conclusions: In a primary care-based incidence cohort of patients with PsA, there were substantial risks of developing uveitis and/or Crohn's disease, but not ulcerative colitis, when compared with the general population and psoriasis controls.